The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1016/s0008-6363(00)00270-4
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes coexpress endothelial and macrophagocytic lineage markers and form cord-like structures in Matrigel® under angiogenic conditions

Abstract: The present data indicate that under angiogenic stimulation macrophages develop an endothelial phenotype with expression of specific surface markers and even form cord- and tubular-like structures in vitro suggesting that this cell population may be recruited for vasculogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
252
3
6

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 390 publications
(275 citation statements)
references
References 23 publications
13
252
3
6
Order By: Relevance
“…We also demonstrated that transplantation of both culture-expanded EPCs from MNCs and C6 glioma augmented neovascularization in experimental animals-bearing tumor, which was similar with other reports [26,27], though the culture condition of EPCs is different between our study and other’. We also found that previous studies all employed rat tail collagen fibronectin matrix as solid braces injected subcutaneously into the subject animals, but it was reported that Matrigel could induce cord formation from several non-endothelial cells including fibroblasts [28], baby murine kidney cells [29], aortic smooth muscle cells, murine leydig cells [30], and CD14 + monocytes seeded in Matrigel [31]. …”
Section: Discussionmentioning
confidence: 86%
“…We also demonstrated that transplantation of both culture-expanded EPCs from MNCs and C6 glioma augmented neovascularization in experimental animals-bearing tumor, which was similar with other reports [26,27], though the culture condition of EPCs is different between our study and other’. We also found that previous studies all employed rat tail collagen fibronectin matrix as solid braces injected subcutaneously into the subject animals, but it was reported that Matrigel could induce cord formation from several non-endothelial cells including fibroblasts [28], baby murine kidney cells [29], aortic smooth muscle cells, murine leydig cells [30], and CD14 + monocytes seeded in Matrigel [31]. …”
Section: Discussionmentioning
confidence: 86%
“…According to their initial discovery, EPCs were defined as cells positive for both hematopoietic stem cell markers such as CD34 and the endothelial marker protein KDR (Asahara et al 1997). However, increasing evidence suggests that myeloid cells can also give rise to endothelial cells (Rehman et al 2003;Gulati et al 2003;Romagnani et al 2005;Burger et al 2002;Fernandez Pujol et al 2000;Schmeisser et al 2001). Also, a recently identified population of peripheral blood-derived CD34 − CD133 + KDR + cells may differentiate into CD34 + CD133 + KDR + and eventually mature EC (Friedrich et al 2006).…”
Section: Determinants Of Circulating Cd14 + -Epcs Levelsmentioning
confidence: 99%
“…However, EPCs defined in this way represent a mixed population since it has become clear that at least two types of endothelial-lineage cells can be obtained from the in vitro culture of mononuclear cells (Rehman et al 2003;Hur et al 2004). Early EPCs, termed circulating angiogenic cells (CACs), are derived mainly from monocytic cells co-expressing some endothelial markers (Rehman et al 2003;Romagnani et al 2005;Fernandez Pujol et al 2000;Schmeisser et al 2001;Hur et al 2004). Early EPCs secrete large amounts of angiogenic growth factors (Rehman et al 2003;Hur et al 2004).…”
Section: Determinants Of Circulating Cd14 + -Epcs Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…They can develop an EC phenotype, especially when stimulated by VEGF and/or bFGF (Fernandez Pujol et al, 2000;Zhao et al, 2003), and produce a functional capillary-like mesh (Schmeisser et al, 2001) permeable by blood cells (Anghelina et al, 2004), hence recapitulating embryo vasculogenesis (Risau et al, 1988). Unlike these reports on the vascular ability by monocytes, mature macrophages have been found to form capillary-like lumina and branching patterns in vitro, confirming their propensity to participate to the de novo formation of microvessels (Anghelina et al, 2006b).…”
Section: Introductionmentioning
confidence: 99%